Making lightweight SiC(rGO, xMoSi2) bulk ceramics via polymeric precursor route. Issue 5 (5th January 2021) - Yao, Rongqian; Zheng, Yinong; Jin, Chao; Huang, Wenyan; Han, Yuchen; Li, Ke; Lan, Siqi; Huang, Zhenguo; Hu, Jiahao; Zhang, Yinggan
Abstract: Unique properties of MoSi2 open new opportunities for preparing bulk polymer‐derived ceramics (PDCs) displaying favorable structural‐functional capabilities. Herein, an ingenious production route via re‐pyrolysis process of ball‐milling‐induced rigid SiC(rGO, x MoSi2 )p fillers/flexible polycarbosilane‐vinyltriethoxysilane‐graphene oxide (PCS‐VTES‐GO, PVG) precursors blends is proposed to obtain in situ formed SiC(rGO, x MoSi2 ) bulk PDCs. Interestingly, the possible dense β‐SiC/SiO x C y /Cfree (rGO, x MoSi2 ) framework suffers load and tiny microsized pores relaxes stress, which is beneficial to providing optimized hardness and fracture toughness, ceramic yield, and linear shrinkage. Attractively, MoSi2 prominently enhances thermal and electrical conductivities of the products owing to increased continuity and compactness. To the best of our knowledge, lightweight SiC(rGO, 20%MoSi2 ) bulk PDCs own brilliant ceramic yield (92.13%), liner shrinkage (6.69%), hardness (10.34 GPa), fracture toughness (4.35 Mpa·m 1/2 ), and thermal conductivity (8.57 W·m –1 ·K –1 ), opening potential emerging uses in aerospace fields.